Intervensi Fisik Tempat Cuci Tangan Pakai Sabun (CTPS) Di Desa Tabongo Kecamatan Dulupi Kabupaten Boalemo - Safrudin Tolinggi; Herman Hatta; Dwi Isnawati; Nur Ain (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2021)
Desa Tabongo is an area in Kecamatan Dulupi, Kabupaten Boalemo and boundries with Desa Dulupi in the north and Tomini Sea in the east. In 2021, the population of Desa Tabongo around 1038 people. Standard effort for preventing infectious disease such as hand washing regularly, practicing good cough and sneeze etiquette, avoiding direct contact with wild animal and livestock, and avoiding close contact with someone who is sick or within symptoms a respiratory disease. Based on observational data in location was found a lack of people awareness for maintaining their health, there was no adequate hand wash facilities. The benefit of community service was a consideration idea for people and related institutions to improve a quality of health within utilizing a materials were available in nature as a primary material for made a hand wash facilites. The purpose of this services was a pilot project of hand washing facilities optimization for increasing a hand washing facilities and solved an increasing case of transmitted and infectious diseasein Desa Tabongo.